Book Review: Eaton E.R. 2021: Wasps: The Astonishing Diversity of a Misunderstood Insect. - M. RINDOŠ (European Journal of Entomology)
Eaton E.R. 2021: Wasps: The Astonishing Diversity of a Misunderstood Insect. Princeton University Press, Princeton and Oxford, v+256 pp. ISBN 9780691211428. Hardcover. Price USD 29.95.